Judicial independence and judges’ irremovability: The case of Gutiérrez Navas et al. v. Honduras (IACHR, Judgment of November 29, 2023 (Merits, Reparations and Costs) - Fernández de Casadevante Romani, Carlos (2025)
In light of the Judgment of the Inter-American Court of Human Rights in the Case of Gutiérrez Navas et al. v. Honduras (Merits, Reparations and Costs) of 29 November 2023, this paper analyses the jurisprudence of the Inter-American Court of Human Rights on judicial independence and irremovability of judges. In the specific case, four judges of the Constitutional Chamber of the Supreme Court of Justice of Honduras were arbitrarily dismissed by a consensual decision between the President of the Republic, the President of the National Congress and the President of the Supreme Court of Justice itself as a political reaction to judgments handed down by the Court within the framework of its constitutional powers that these powers considered contrary to their interests. The events took place on 12 December 2012 and eleven years later the Court declared the violation of various rights of the American Convention on Human Rights. The Judgment is preceded by Honduras' acknowledgement of the violation of the rights invoked by the victims and declared by the Inter-American Commission on Human Rights, with the exception of the right to personal integrity linked to the threats and harassment to which the victims were subjected. This violation is being examined by the Court. The judgment constitutes a new contribution by the Court to the preservation of judicial independence and the irremovability of judges, fundamental pillars of democracy and the rule of law. It continues the path of precedent decisions of the Court handed down in relation to other states of the Inter American system and contributes to the institutionalisation of the democratic system in Honduras.